FOXC1 Negatively Regulates DKK1 Expression to Promote Gastric Cancer Cell Proliferation Through Activation of Wnt Signaling Pathway - Jiang, Jiang; Li, Jianfang; Yao, Weiwu; Wang, Wenfang; Shi, Bowen; Yuan, Fei; Dong, Jingyan; Zhang, Huan (Frontiers in Cell and Developmental Biology, 2021)
Gastric cancer (GC), characterized by uncontrolled growth, is a common malignant tumor of the digestive system. The Wnt signaling pathway plays an important role in the tumorigenesis and proliferation of GC. Many studies on this signaling pathway have focused on its intracellular regulatory mechanism, whereas little attention has been given to extracellular regulatory factors. DKK1 is the most important extracellular Wnt antagonist protein, and it can bind with LRP5/6 to inhibit activation of the Wnt pathway. However, the regulation and mechanism of DKK1 in the proliferation of GC remain unclear. FOXC1 plays an important role in organ development and tumor growth, but its role in GC tumor growth remains unknown. In this study, we found that the FOXC1 is highly expressed in patients with GC and high expression of FOXC1 correlates to poor prognosis. In addition, we found that the Wnt signaling pathway in GC cells with high FOXC1 expression was strongly activated. FOXC1 negatively regulates DKK1 expression by binding to its promoter region, thereby promoting the activation of Wnt pathway. FOXC1 can also form a complex with the β-catenin in the cytoplasm and then dissociates from β-catenin in the nucleus, thereby promoting the entry of β-catenin into the nucleus and regulating expression of c-MYC, which promotes the proliferation of GC cells. Our study not only reveals the function and mechanism of FOXC1 in GC, but also provides a potential target for clinic GC treatment.